2020
DOI: 10.1111/gcb.15402
|View full text |Cite
|
Sign up to set email alerts
|

Climate change facilitates a parasite’s host exploitation via temperature‐mediated immunometabolic processes

Abstract: Global climate change can influence organismic interactions like those between hosts and parasites. Rising temperatures may exacerbate the exploitation of hosts by parasites, especially in ectothermic systems. The metabolic activity of ectotherms is strongly linked to temperature and generally increases when temperatures rise. We hypothesized that temperature change in combination with parasite infection interferes with the host's immunometabolism. We used a parasite, the avian cestode Schistocephalus solidus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 79 publications
(108 reference statements)
1
15
0
Order By: Relevance
“…However, we recently observed an impact of exposure on threespine stickleback hepatosomatic index and body condition, traditionally used as a measure of host condition (Chellappa et al, 1995; Piecyk, Ritter, et al, 2019). Likewise, a recent study showed a equally strong impact of exposure and infection on the liver transcriptome, with an increase in expression of genes involved in cellular turnover and metabolic processes (Scharsack et al, 2021). This reduced host condition and shift in metabolic activity upon exposure suggests that the cost of resistance to infection, and elimination of the parasite through cell‐mediated immunity within the first 2 weeks of infection (Kurtz et al, 2004) could indirectly impact the microbiome of exposed sticklebacks.…”
Section: Discussionmentioning
confidence: 97%
“…However, we recently observed an impact of exposure on threespine stickleback hepatosomatic index and body condition, traditionally used as a measure of host condition (Chellappa et al, 1995; Piecyk, Ritter, et al, 2019). Likewise, a recent study showed a equally strong impact of exposure and infection on the liver transcriptome, with an increase in expression of genes involved in cellular turnover and metabolic processes (Scharsack et al, 2021). This reduced host condition and shift in metabolic activity upon exposure suggests that the cost of resistance to infection, and elimination of the parasite through cell‐mediated immunity within the first 2 weeks of infection (Kurtz et al, 2004) could indirectly impact the microbiome of exposed sticklebacks.…”
Section: Discussionmentioning
confidence: 97%
“…These extreme climatic conditions can result in direct mortality (Hall & Sun, 2021; Sun et al., 2021), or indirectly depress survival by imposing physiological stress, weakening immunocompetence and resistance to parasites (e.g. Scharsack et al., 2021; Sun, Wang, et al., 2018; Wang et al., 2016; Zhang et al., 2018). Alternatively, the higher survival rate of hatchlings in warming climates might be due to treatment‐induced enhancement in performance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the authors have used a correlational, natural experimental approach to investigate whether temperature is associated with the outcome of infection for both a wild stickleback host and its cestode parasite. Previous laboratory work found that high temperatures benefitted the parasite while being detrimental to the host (Macnab & Barber, 2012; Scharsack et al ., 2021). Nonetheless, in wild, free‐ranging fish, the authors found little evidence that the outcome of the host–parasite interaction was linked with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the authors did not observe an increase in parasite size through time indicates that hosts with large parasites disappearing from the population were balanced by new infections, with smaller parasites, being established at a similar rate. If infections were established substantially before this study began, then the prevalences observed could also be affected by temperatures at the time of initial exposure, which can affect the success of S. solidus establishment (Scharsack et al ., 2021). Moreover, infection outcomes depend on the hosts’ temperature of origin, such that hosts are less tolerant of infection at unfamiliar temperatures (Franke et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation